The Speculative Demand for Securities and Carry-Over - Turvey, Ralph (Review of Economic Studies, 1951)
Journal Article The Speculative Demand for Securities and Carry-Over Get access Ralph Turvey Ralph Turvey London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 1, 1950, Pages 61–65, https://doi.org/10.2307/2296272 Published: 01 December 1950